Validation of phylogenetic informative Y-InDels in Y-chromosomal haplogroup O-M175 - Zhou, Zhihan; Li, Zhimin; Yao, Yining; Qian, Jinglei; Ji, Qiqi; Shao, Chengchen; Xie, Jianhui (Frontiers in Genetics, 2023)
The Y-chromosomal haplogroup tree, which consists of a group of Y-chromosomal loci with phylogenetic information, has been widely applied in anthropology, archaeology and population genetics. With the continuous updating of the phylogenetic structure, Y-chromosomal haplogroup tree provides more information for recalling the biogeographical origin of Y chromosomes. Generally, Y-chromosomal insertion-deletion polymorphisms (Y-InDels) are genetically stable as Y-chromosomal single nucleotide polymorphisms (Y-SNPs), and therefore carry mutations that can accumulate over generations. In this study, potential phylogenetic informative Y-InDels were filtered out in haplogroup O-M175, which is dominant in East Asia, based on population data retrieved from the 1000 Genomes Project. A group of 22 phylogenetic informative Y-InDels were identified and then assigned to their corresponding subclades of haplogroup O-M175, which provided a supplement for the update and application of Y-chromosomal markers. Especially, four Y-InDels were introduced to define subclades determined using a single Y-SNP.